TRANSFORMATION IN THE ART OF ACTING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the issue of transformation in the art of acting, the ways in which an actor temporarily sets aside their own personality to become another character and transitions into a different psychological state.